2014
DOI: 10.1007/s12192-014-0503-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity, population structure and stress protein-based capacitoring in populations of Xeropicta derbentina, a heat-tolerant land snail species

Abstract: The shell colour of many pulmonate land snail species is highly diverse. Besides a genetic basis, environmentally triggered epigenetic mechanisms including stress proteins as evolutionary capacitors are thought to influence such phenotypic diversity. In this study, we investigated the relationship of stress protein (Hsp70) levels with temperature stress tolerance, population structure and phenotypic diversity within and among different populations of a xerophilic Mediterranean snail species (Xeropicta derbenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Furthermore, the capacity to induce Hsp70 depends on the physiological status of an individual, as warm‐adapted Theba pisana showed maximal hsp70 ‐mRNA induction at higher temperatures and also higher upper thermal limits of hsp mRNA synthesis (Mizrahi, Goldenberg, Heller, & Arad, ). Thus, different species or populations seem to differ in their strategies to cope with heat stress at the molecular level, a finding that has also been confirmed by Di Lellis et al (). Concerning temperature‐correlated seasonal variability of Hsp70 levels in Xeropicta derbentina in the field, Dieterich et al () found the Hsp70 level to be positively correlated with shell surface temperature in April, June, and August only, while a negative correlation was observed in October.…”
Section: Molecular Adaptationssupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, the capacity to induce Hsp70 depends on the physiological status of an individual, as warm‐adapted Theba pisana showed maximal hsp70 ‐mRNA induction at higher temperatures and also higher upper thermal limits of hsp mRNA synthesis (Mizrahi, Goldenberg, Heller, & Arad, ). Thus, different species or populations seem to differ in their strategies to cope with heat stress at the molecular level, a finding that has also been confirmed by Di Lellis et al (). Concerning temperature‐correlated seasonal variability of Hsp70 levels in Xeropicta derbentina in the field, Dieterich et al () found the Hsp70 level to be positively correlated with shell surface temperature in April, June, and August only, while a negative correlation was observed in October.…”
Section: Molecular Adaptationssupporting
confidence: 67%
“…Thus, even within a species, apparent local ecological peculiarities seem to result in microevolutionary consequences regarding snails' molecular adaptations to heat. Interestingly, these interpopulation differences in the constitutive and maximal Hsp70 levels correlated with the variation in the shell coloration pattern in these Xeropicta populations (Di Lellis et al, ) which, in turn, may have consequences for the average thermal capacity of individuals from these populations (if intensely pigmented shells actually lead to higher body temperature). Furthermore, this observation strengthened the concept of Hsps as epigenetic capacitors of phenotypic variation (Di Lellis et al, ) as variation in coloration correlated inversely with the Hsp70 level in a number of Xeropicta derbentina populations from southern France: There was little color variation in populations exhibiting high Hsp70 levels and greater color variation in populations with low Hsp70 levels.…”
Section: Molecular Adaptationsmentioning
confidence: 91%
See 1 more Smart Citation
“…As protein integrity is mandatory for a cell's survival, a biochemical chaperoning machinery that assists in protein (re)folding has been established early in the evolution of life. A central component of this machinery is the Hsp70 protein family, whose induction by heat and drought has been well characterized in land snails (Arad et al., 2010; Di Lellis et al., 2014; Dieterich et al., 2013, 2015; Gaitán‐Espitia et al., 2013; Köhler et al., 2009; Kotsakiozi et al., 2015; Mizrahi et al., 2010, 2011, 2012a, 2012b, 2015, 2016; Scheil et al., 2011; Troschinski, et al., 2014). As long as an induction of Hsp70 may compensate for the proteotoxic impact of body temperature elevation, organisms can limit pathologies and ensure survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, species identification of snails is not so trivial, when based essentially on morphological criteria. The morphological polymorphism, inter and intra-specific, is extremely important in terrestrial snails depending on many parameters such as age, season, environmental conditions and biochemical factors [ 42 - 47 ]. Recently, using of molecular tools, by studying domains such as internal transcribed spacer and 18S rDNA or the COI and 16S mDNA, have facilitated the recognition of snails at a specific level.…”
Section: Introductionmentioning
confidence: 99%